Correlative multi-scale cryo-imaging unveils SARS-CoV-2 assembly and egress - Luiza Mendonça (Nature Portfolio, 2021)
In this study, Peijun Zhang and colleagues use cryoFIB/SEM volume imaging and soft x-ray cryo-tomography with cryo-electron tomography (cryoET) of cellular periphery, lamellae, and subtomogram averaging to place critical structural events in the SARS-CoV-2 infection cycle in the context of whole-cell images.